FRAMEWORKS STRATEGIS SEBAGAI FONDASI GREEN BUDGETING: STUDI KASUS KABUPATEN TORAJA UTARA - Yusuf, Yulia Yunita; Rais, Anisatun Humayrah; Adriansyah, Adriansyah; Faisal, Andi (Universitas Ichsan Sidenreng Rappang, 2025)
Strategic frameworks are a key component of the OECD Green Budgeting Framework, aiming to align fiscal policy with environmental sustainability. This study evaluates the implementation of strategic frameworks in policy documents in North Toraja Regency, including the Strategic Plan (Renstra), Strategic Environmental Assessment (KLHS), and the Regional Government Work Plan (RKPD). Using Krippendorff's content analysis approach, the study identifies key themes across three dimensions: semantics, pragmatics, and symbolic means. The findings reveal that although the policy documents reflect a commitment to sustainability, there are significant shortcomings, including the absence of measurable performance indicators, sufficient baseline data, and clear evaluation mechanisms. From a pragmatic perspective, program implementation is often hindered by a lack of cross-sectoral coordination and inadequate budget allocation. Furthermore, the analysis of symbolic means indicates that the information presented in the documents is more focused on administrative outputs rather than outcomes that reflect real impact. This study concludes that the strategic frameworks in North Toraja Regency need to be strengthened through more technical approaches, including the development of specific performance indicators, enhanced coordination among local government agencies, and the integration of data-based evaluation mechanisms. These recommendations are expected to improve the effectiveness of policy documents in supporting the sustainable implementation of green budgeting at the local level.